In situ polymerized polyetherimide/Al2O3 nanocomposites with significantly improved capacitive energy storage performance at high temperatures - Li Tan; Jiufeng Dong; Li Li; Chengyuan Wang; Yuqi Liu; Yujuan Niu; Zizhao Pan; Liang Sun; Hong Wang (Journal of Materiomics)
High-temperature polymer nanocomposites with high energy storage density (Ue) are promising dielectrics for capacitors used in electric vehicles, aerospace, etc. However, filler agglomeration and interface defects at high filler loadings significantly limit the enhancement of Ue and hamper the large-scale production of the nanocomposites. Here, polyetherimide (PEI) nanocomposites with nanoscale alumina (AO) at ultra-low contents were prepared via in situ polymerization from PEI monomers. We compared two composite dielectric preparation methods (in situ polymerization and ordinary solution blending) under the same conditions. In contrast to the nanocomposites obtained by blending PEI polymers with AO, the in situ nanocomposites exhibit substantially improved filler dispersion, together with largely suppressed conduction loss at high fields and high temperatures, leading to comprehensive enhancements of breakdown strength (Eb), charge-discharge efficiency (η) and Ue, simultaneously. The 0.3% (in volume) AO filled PEI nanocomposite film exhibits a superior Ue of 4.8 J/cm3 with η of 90% at 150 °C, which is 128% and 218% higher than those of pristine PEI and the ex situ PEI/AO nanocomposite film under the same conditions, respectively. This work provides a scalable strategy for the preparation of dielectrics with both good processability and excellent high-temperature energy storage performance.